Engineering artificial small RNAs for conditional gene silencing in escherichia coli - Tan, Tong Wei (2014)
Conditional gene silencing is a promising technology within the microbiology field. Silencing a gene from a bacteria or cell will greatly change the cell function and morphology. This can be achieved using RNA interference technologies such as small regulatory RNAs (sRNA). However, the specificity of sRNA remains a huge challenge in effective adoption of sRNA in conditional gene silencing as it may have huge amounts of off target activity. Here I discuss the potential application of conditional gene silencing in modulating the death pathways of Escherichia coli. By attenuating the death pathways within E. coli, there could potentially improve cell viability.